Autophagy: A Key Regulator of Homeostasis and Disease: An Overview of Molecular Mechanisms and Modulators - Laura Gómez-Virgilio; Maria-del-Carmen Silva-Lucero; Diego-Salvador Flores-Morelos; Jazmin Gallardo-Nieto; Gustavo Lopez-Toledo; Arminda-Mercedes Abarca-Fernandez; Ana-Elvira Zacapala-Gómez; José Luna-Muñoz; Francisco Montiel-Sosa; Luis O. Soto-Rojas; Mar Pacheco-Herrero; Maria-del-Carmen Cardenas-Aguayo (Cells, 2022)
Autophagy is a highly conserved lysosomal degradation pathway active at basal levels in all cells. However, under stress conditions, such as a lack of nutrients or trophic factors, it works as a survival mechanism that allows the generation of metabolic precursors for the proper functioning of the cells until the nutrients are available. Neurons, as post-mitotic cells, depend largely on autophagy to maintain cell homeostasis to get rid of damaged and/or old organelles and misfolded or aggregated proteins. Therefore, the dysfunction of this process contributes to the pathologies of many human diseases. Furthermore, autophagy is highly active during differentiation and development. In this review, we describe the current knowledge of the different pathways, molecular mechanisms, factors that induce it, and the regulation of mammalian autophagy. We also discuss its relevant role in development and disease. Finally, here we summarize several investigations demonstrating that autophagic abnormalities have been considered the underlying reasons for many human diseases, including liver disease, cardiovascular, cerebrovascular diseases, neurodegenerative diseases, neoplastic diseases, cancers, and, more recently, infectious diseases, such as SARS-CoV-2 caused COVID-19 disease.